Spherical black holes with minimally coupled scalar cloud/hair in Einstein–Born–Infeld gravity - Zhang, Shao-Jun (The European physical journal. C, Particles and fields, 2022)
Previous studies showed that, in the presence of a simple and well-motivated self-interaction scalar potential, asymptotically flat and spherical black holes can carry minimally coupled and charged scalar cloud/hair in Einstein–Maxwell gravity. We extend these studies to Einstein–Born–Infeld gravity to consider the effect of nonlinearity of the electromagnetic field. Series of spherical cloudy/hairy black hole solutions are constructed numerically. Results show that increasing the Born–Infeld coupling constant b will make the domain of existence of the solution shrink or even disappear when b is large enough. This implies that, competing with the gravitation, nonlinearity of the electromagnetic field will make the formation of scalar cloud/hair harder or even impossible.